A barrier film and its preparation method and application
By using a polyurethane film substrate containing soft segments in the inflatable material and filling the core-shell structure filler, the problem of high photothermal transmittance of the inflatable material is solved, efficient photothermal and gas barrier is achieved, and the safety of the inflatable equipment is improved. Sex and stability.
Patent Information
- Application Number
- CN202411284391.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing inflatable materials have high sunlight transmittance, which leads to an increase in the temperature of the surface and internal gases, resulting in an overheating and overpressure problem. At the same time, the thermal effect will also lead to local stress concentration and the aging of the material's thermal oxygen, affecting the safety and stability of the inflatable equipment.
A barrier film is used, which includes a polyurethane containing a soft segment as a film substrate, and a core-shell structure filler with a sheet/rod-shaped natural mineral as the core and titanium dioxide as the shell is filled in the film substrate. The fillers are arranged in a film substrate to improve the photothermal and gas barrier properties.
It achieves excellent photothermal control and gas barrier capabilities, reduces the temperature and internal pressure of the inflatable material, and improves the safety and stability of the inflatable equipment.
Smart Images

Figure CN118791867B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material chemistry, and in particular relates to a barrier film and a preparation method and application thereof. Background Art
[0002] Airships, moored balls and other aerostats or inflatable buildings are usually composed of multi-layer structures, including at least a weather-resistant layer, a barrier layer, a load-bearing layer and a heat-sealing layer from the outside to the inside. Due to the requirement of lightweight, the weather-resistant layer with light-blocking particles only accounts for 140~300g / m 2 ) is 10~20wt%. Therefore, the high solar transmittance of the inflatable material not only increases the surface temperature of the inflatable material, but also increases the temperature of the internal gas, causing the inflatable bag to have overheating and overpressure problems. At the same time, the thermal effect will also lead to local stress concentration and thermal oxidation aging of the material, affecting the safety and stability of the inflatable equipment.
[0003] At present, the most commonly used barrier layers for inflatable materials are PET and EVOH films, which have high surface energy and are brittle, requiring high bonding technology and greatly reducing the rubbing resistance of the inflatable materials. In addition, transparent PET, EVOH and other resin barrier layers do not contribute to the light and heat barrier of the material. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a barrier film and a preparation method and application thereof. The barrier film provided by the present invention has both excellent light and heat control capabilities and gas barrier capabilities.
[0005] The present invention provides a barrier film, comprising: a film substrate and a filler filled in the film substrate; wherein the film substrate is a polyurethane containing a soft segment, and the soft segment is a polydimethylsiloxane segment and a polyethylene glycol segment; the filler is a core-shell structure, the outer shell is titanium dioxide, the inner core is a natural mineral, and the shape of the inner core is sheet and / or rod; the filling amount of the filler in the barrier film is 30-65wt%.
[0006] Preferably, the molar ratio of the polydimethylsiloxane chain segment to the polyethylene glycol chain segment is 1:(1-10).
[0007] Preferably, the natural mineral is one or more of sepiolite, kaolin, mica, talc, expanded vermiculite, expanded perlite, diatomaceous earth, palygorskite and halloysite nanotubes.
[0008] Preferably, the thickness of the flaky inner core is 20-100 nm, and the dimension perpendicular to the thickness direction is 1-20 μm; the length of the rod-shaped inner core is 1-10 μm, and the diameter is 20-500 nm.
[0009] Preferably, the titanium dioxide content of the filler is 20-40wt%.
[0010] The present invention provides a method for preparing the barrier film described in the above technical solution, comprising the following steps:
[0011] The filler is mixed with the film base material solution, coated, and dried to obtain a barrier film.
[0012] Preferably, the filler is prepared according to the following steps:
[0013] The acidic dispersion of the core material is mixed with tetrabutyl titanate to react to obtain a solid product;
[0014] The solid product is calcined and crushed to obtain a core-shell structure filler with titanium dioxide as the outer shell.
[0015] Preferably, the membrane substrate solution is prepared according to the following steps:
[0016] Prepolymerizing diisocyanate, dihydroxy-terminated polydimethylsiloxane and polyethylene glycol in a solvent to obtain a prepolymer;
[0017] The prepolymer is mixed with the chain extender for reaction, and after the reaction is completed, the solid content of the reaction product is adjusted with a solvent to obtain a polyurethane film substrate solution containing a soft segment.
[0018] Preferably, the coating method is multiple scraping.
[0019] The present invention provides an inflatable bladder, the material of which includes the barrier film described in the above technical solution or the barrier film prepared by the preparation method described in the above technical solution.
[0020] Compared with the prior art, the present invention provides a barrier film and its preparation method and application. The barrier film provided by the present invention includes a film substrate and a filler filled in the film substrate; wherein the film substrate is a polyurethane containing a soft segment, and the soft segment is a polydimethylsiloxane segment and a polyethylene glycol segment; the filler is a core-shell structure, the outer shell is titanium dioxide, the inner core is a natural mineral, and the shape of the inner core is a sheet and / or a rod; the filling amount of the filler in the barrier film is 30~65wt%. The present invention uses a polyurethane containing a soft segment as a film substrate. Due to the presence of Si-O bonds in the polydimethylsiloxane (PDMS) segment in the soft segment and COC bonds in the polyethylene glycol (PEG) segment, the infrared emissivity of the film material at the atmospheric window can be improved, which has a positive effect on improving the light and heat control ability; at the same time, the crystallization performance of PEG can improve the gas barrier performance to a certain extent, and has reversible temperature regulation performance. On this basis, the present invention adopts a core-shell structure filler with a flake or rod-shaped natural mineral as the core and titanium dioxide as the shell as the filling material of the film material. These fillers can be oriented in the film substrate. When light is irradiated to the filler, multiple refractions and diffractions will occur, thereby improving the light barrier performance of the film material; at the same time, the oriented filler can also extend the diffusion path of the gas, thereby improving the gas barrier performance of the film material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 is a scanning electron microscope image of HNTs@TiO2 prepared in Example 1 provided by the present invention;
[0023] Figure 2 is a scanning electron microscope image of the barrier film prepared in Example 1 provided by the present invention;
[0024] Figure 3 is a scanning electron microscope image of talc powder@TiO2 prepared in Example 11 provided by the present invention;
[0025] Figure 4 is a scanning electron microscope image of the barrier film prepared in Example 11 provided by the present invention;
[0026] Figure 5 This is the infrared emissivity test spectrum provided by the present invention. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a barrier film, comprising: a film substrate and a filler filled in the film substrate; wherein the film substrate is a polyurethane containing a soft segment, and the soft segment is a polydimethylsiloxane segment and a polyethylene glycol segment; the filler is a core-shell structure, the outer shell is titanium dioxide, the inner core is a natural mineral, and the shape of the inner core is sheet and / or rod.
[0029] In the barrier film provided by the present invention, in the film substrate, the number average molecular weight of the polydimethylsiloxane segment is preferably 500-2000, more preferably 800-1500, and specifically 1000; the number average molecular weight of the polyethylene glycol segment is preferably 2000-8000, more preferably 3000-5000, and specifically 4000; the molar ratio of the polydimethylsiloxane segment to the polyethylene glycol segment is preferably 1:(1-10), and specifically 1:1, 1:5 or 1:10; the molar ratio of the total molar amount of the polydimethylsiloxane segment and the polyethylene glycol segment to the repeating unit corresponding to the diisocyanate in the polyurethane is preferably (0.5-1.5):2, more preferably (0.8-1.2):2, and specifically 1:2.
[0030] In the barrier film provided by the present invention, the core shape of the filler is flake and / or rod-shaped; wherein the flake thickness of the flake core is preferably 20~100nm, and the dimension perpendicular to the thickness direction is preferably 1~20μm; the length of the rod-shaped core is preferably 1~10μm, and the diameter is preferably 20~500nm.
[0031] In the barrier film provided by the present invention, the inner core of the filler is a natural mineral, preferably one or more of sepiolite, kaolin, mica, talc, expanded vermiculite, expanded perlite, diatomite, palygorskite and halloysite nanotubes; wherein the halloysite nanotubes, sepiolite and palygorskite are rod-shaped inner cores, and the kaolin, mica, talc, expanded vermiculite, expanded perlite and diatomite are flaky inner cores.
[0032] In the barrier film provided by the present invention, in the preferred natural mineral filler core, the length of the sepiolite is preferably 1-10 μm, more preferably 2-5 μm, and the diameter is preferably 100-500 nm; the thickness of the kaolin is preferably 20-50 nm, and the dimension perpendicular to the thickness direction is preferably 1-5 μm, more preferably 2-3 μm; the thickness of the mica is preferably 50-100 nm, and the dimension perpendicular to the thickness direction is preferably 5-20 μm, more preferably 10-15 μm; the thickness of the talc is preferably 30-60 nm, and the dimension perpendicular to the thickness direction is preferably 5-20 μm, more preferably 10-15 μm; the thickness of the expanded vermiculite is preferably 20-50 nm, and the dimension perpendicular to the thickness direction is preferably 2-15 μm, more preferably 4~10μm; the thickness of the expanded perlite is preferably 20~40nm, and the dimension perpendicular to the thickness direction is preferably 2~15μm, more preferably 4~10μm; the thickness of the diatomite is preferably 30~50nm, and the dimension perpendicular to the thickness direction is preferably 2~10μm, more preferably 3~8μm; the length of the palygorskite is preferably 1~10μm, more preferably 2~5μm, and the diameter is preferably 100~200nm; the length of the halloysite nanotube is preferably 1~8μm, more preferably 2~4μm, the inner cavity diameter of the halloysite nanotube is preferably 20~150nm, more preferably 40~100nm, and the outer diameter of the halloysite nanotube is preferably 30~180nm, more preferably 50~120nm.
[0033] In the barrier film provided by the present invention, the outer shell of the filler is titanium dioxide; the titanium dioxide content of the filler is preferably 20-40wt%, more preferably 25-35wt%, and specifically 30wt%.
[0034] In the barrier film provided by the present invention, the filling amount of the filler in the barrier film is preferably 30-65wt%, specifically 30wt%, 50wt% or 65wt%.
[0035] In the barrier film provided by the present invention, the thickness of the barrier film is preferably 40-120 μm, specifically 40 μm, 80 μm or 120 μm.
[0036] The present invention provides a method for preparing the barrier film described in the above technical solution, comprising the following steps:
[0037] The filler is mixed with the film base material solution, coated, and dried to obtain a barrier film.
[0038] In the preparation method provided by the present invention, the filler is preferably prepared according to the following steps:
[0039] The acidic dispersion of the core material is mixed with tetrabutyl titanate to react to obtain a solid product;
[0040] The solid product is calcined and crushed to obtain a core-shell structure filler with titanium dioxide as the outer shell.
[0041] In the above-mentioned filler preparation steps provided by the present invention, the solvent in the acidic dispersion is preferably ethanol; the content of the core material in the acidic dispersion is preferably 0.5~50g / L, preferably 10~40g / L, specifically 30g / L; the pH value of the acidic dispersion is preferably 3~4; the acidic dispersion of the core material is preferably obtained by dispersing the core material into a solvent and then adjusting the pH value, and the reagent for adjusting the pH value is preferably dilute hydrochloric acid.
[0042] In the above-mentioned filler preparation steps provided by the present invention, the butane titanate is preferably mixed in the form of a butane titanate solution; the solvent in the butane titanate solution is preferably ethanol; the concentration of the butane titanate solution is preferably 5~30vol%, more preferably 8~20vol%, specifically 10vol%; the mixing method is preferably to add the butane titanate solution dropwise to the acidic dispersion of the core material.
[0043] In the above-mentioned filler preparation step provided by the present invention, the temperature of the mixing reaction is preferably 10~40°C, more preferably 15~30°C, and specifically 25°C (room temperature); the time of the mixing reaction is preferably 3~8h, more preferably 3.5~6h, and specifically 4h.
[0044] In the filler preparation step provided by the present invention, after the mixing reaction is completed, the product is washed, filtered and dried for multiple times to obtain a solid product.
[0045] In the above-mentioned filler preparation steps provided by the present invention, the calcination temperature is preferably 600-900° C., more preferably 600-700° C.; the calcination time is preferably 6-10 h, more preferably 6-8 h.
[0046] In the filler preparation step provided by the present invention, the content of titanium dioxide on the filler can be regulated by controlling the mixing reaction time.
[0047] In the preparation method provided by the present invention, the filler is preferably mixed in the form of a filler dispersion; the solvent in the filler dispersion includes but is not limited to N,N-dimethylformamide (DMF) and / or tetrahydrofuran (THF).
[0048] In the preparation method provided by the present invention, the solid content of the membrane substrate solution is preferably 20-40wt%, more preferably 25-35wt%, and specifically 30wt%; the solvent in the membrane substrate includes but is not limited to N,N-dimethylformamide (DMF) and / or tetrahydrofuran (THF).
[0049] In the preparation method provided by the present invention, the membrane substrate solution is prepared according to the following steps:
[0050] Prepolymerizing diisocyanate, dihydroxy-terminated polydimethylsiloxane and polyethylene glycol in a solvent to obtain a prepolymer;
[0051] The prepolymer is mixed with the chain extender for reaction, and after the reaction is completed, the solid content of the reaction product is adjusted with a solvent to obtain a polyurethane film substrate solution containing a soft segment.
[0052] In the above-mentioned membrane substrate solution preparation step provided by the present invention, the diisocyanate includes but is not limited to hexamethylene diisocyanate (HDI); the molar ratio of the dihydroxy-terminated polydimethylsiloxane and polyethylene glycol is preferably 1: (1-10), specifically 1: 1, 1: 5 or 1: 10; the molar ratio of -NCO of the isocyanate to -OH of the dihydroxy-terminated polydimethylsiloxane and polyethylene glycol is preferably 2: (0.5-1.5), more preferably 2: (0.8-1.2), specifically 2: 1; the solvent includes but is not limited to N, N-dimethylformamide (DMF) and / or tetrahydrofuran (THF).
[0053] In the above-mentioned membrane substrate solution preparation step provided by the present invention, the temperature of the prepolymerization reaction is preferably 60-80° C., more preferably 70-80° C.; the time of the prepolymerization reaction is preferably 1-3 h, more preferably 1-2 h.
[0054] In the above-mentioned membrane substrate solution preparation step provided by the present invention, the chain extender includes but is not limited to 1,4-butanediol (BDO); the molar ratio of -OH of the chain extender to the remaining -NCO in the prepolymer is preferably 1:1.
[0055] In the above-mentioned membrane substrate solution preparation step provided by the present invention, the temperature of the mixing reaction is preferably 60-80° C., more preferably 70-80° C.; the time of the mixing reaction is preferably 1-2 h, more preferably 1-1.5 h.
[0056] In the preparation method provided by the present invention, the coating method is preferably multiple scraping. In the present invention, multiple scraping is more conducive to the orientation of the filler in the film material and improves the gas barrier performance of the film material.
[0057] In the preparation method provided by the present invention, the drying method is preferably natural drying.
[0058] The present invention also provides an inflatable bladder, the material of which includes the barrier film described in the above technical solution or the barrier film prepared by the preparation method described in the above technical solution.
[0059] The technical solution provided by the present invention uses polyurethane containing soft segments as the film substrate. Due to the presence of Si-O bonds in the polydimethylsiloxane (PDMS) segment and COC bonds in the polyethylene glycol (PEG) segment in the soft segment, the infrared emissivity of the film material at the atmospheric window can be improved, which has a positive effect on improving the light and heat control ability; at the same time, the crystallization performance of PEG can improve the gas barrier performance to a certain extent, and has reversible temperature regulation performance. On this basis, the technical solution provided by the present invention uses a core-shell structure filler with a sheet\rod-shaped natural mineral as the core and titanium dioxide as the shell as the filling material of the film material. These fillers can be oriented in the film substrate. When the light is irradiated to the filler, multiple refractions and diffractions will occur, thereby improving the light barrier performance of the film material; at the same time, the oriented filler can also extend the diffusion path of the gas, thereby improving the gas barrier performance of the film material.
[0060] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0061] Example 1
[0062] A barrier film material is composed of 70wt% of soft-chain polyurethane and 30wt% of filler; wherein the raw materials of the polyurethane are PDMS and PEG, HDI and BDO in a molar ratio of 1:10; the filler is titanium dioxide-coated halloysite nanotubes; and the film thickness is 40μm.
[0063] The preparation method of the above barrier film material is as follows:
[0064] 1. Preparation of fillers:
[0065] 1) Weigh 30 g of halloysite nanotubes (length 2-4 μm, inner diameter 40-100 nm, outer diameter 50-120 nm), disperse them in 1 L of anhydrous ethanol, and add dilute hydrochloric acid to adjust the pH to 3-4;
[0066] 2) Take another beaker, measure 100 mL of tetrabutyl titanate, and add it to 900 mL of anhydrous ethanol to prepare a tetrabutyl titanate solution with a concentration of 10 vol%;
[0067] 3) Add the prepared tetrabutyl titanate solution dropwise to the halloysite dispersion under stirring, stir and react for 4 hours, then wash, filter and dry several times;
[0068] 4) The dried material obtained in step 3) is placed in a tube furnace, calcined at 600°C for 6 hours, and then ground to obtain rutile titanium dioxide-coated halloysite nanotubes (HNTs@TiO2), wherein the TiO2 content is about 30%, the length is 2.2~4.5μm, and the diameter is 70~200nm.
[0069] The scanning electron microscope image of HNTs@TiO2 prepared in this example is as follows Figure 1 As shown, through Figure 1 It can be seen that part of the surface of the halloysite nanotubes is coated with titanium dioxide.
[0070] (II) Preparation of membrane substrate solution:
[0071] 1) Weigh 5 g of PDMS with Mn=1000 and 200 g of PEG4000 with Mn=4000 (molar ratio 1:10), place in a flask at 80°C and vacuum dry to remove water for 2 h;
[0072] 2) Then add 500 mL of DMF and stir to dissolve; then dropwise add 50 g of DMF solution of HDI, wherein HDI is 18.5 g and the molar ratio of NCO to OH is 2:1, and stir to react at 80°C for 2 h;
[0073] 3) The content of the remaining NCO group was confirmed by di-n-butylamine titration. The molar number of the remaining NCO was 0.098 mol. Therefore, 8 g of BDO DMF solution (4.4 g of BDO and a molar ratio of NCO to OH of 1:1) was added dropwise, and the reaction was continued at 80°C for 1 h. After the reaction was completed, the solid content of TPU was adjusted to 30% by adding DMF.
[0074] (III) Preparation of barrier film:
[0075] 12 g of HNTs@TiO2 was weighed, ultrasonically dispersed in 175 g of DMF, and then mixed with 93.3 g of 30 wt% TPU. After stirring and mixing, it was coated 4 times with a 20 μm scraper and dried naturally after each coating to obtain a film with a thickness of 40 μm.
[0076] The scanning electron microscope image of the barrier film prepared in this example is as follows Figure 2 As shown, through Figure 2 It can be seen that the rod-shaped HNTs@TiO2 are filled in the TPU film substrate.
[0077] Embodiment 2-3
[0078] Different from Example 1, in Examples 2-3, the ratios of polyurethane to filler are 50wt%:50wt% and 35wt%:65wt% respectively.
[0079] Embodiment 4-5
[0080] Different from Example 2, in Examples 4-5, the thickness of the film is 80 μm and 120 μm, respectively.
[0081] Embodiment 6-7
[0082] Different from Example 4, in Examples 6-7, the molar ratios of PDMS to PEG in the polyurethane are 1:5 and 1:1, respectively.
[0083] Embodiments 8 to 15
[0084] Different from Example 4, in Examples 8 to 15, the core materials of the fillers are respectively sepiolite (length 2 to 5 μm, diameter 100 to 500 nm), kaolin (thickness 20 to 50 nm, and a dimension perpendicular to the thickness direction of 2 to 3 μm), mica (thickness 50 to 100 nm, and a dimension perpendicular to the thickness direction of 10 to 15 μm), talc (thickness 30 to 60 nm, and a dimension perpendicular to the thickness direction of 10 to 15 μm), expanded vermiculite (thickness 20 to 50 nm, and a dimension perpendicular to the thickness direction of 4 to 10 μm), expanded perlite (thickness 20 to 40 nm, and a dimension perpendicular to the thickness direction of 4 to 10 μm), diatomaceous earth (thickness 30 to 50 nm, and a dimension perpendicular to the thickness direction of 3 to 8 μm), and palygorskite (length 2 to 5 μm, diameter 100 to 200 nm).
[0085] The scanning electron microscope image of talc powder @ TiO2 prepared in Example 11 is as follows Figure 3 As shown, through Figure 3 It can be seen that part of the surface of the flaky talc is coated with titanium dioxide.
[0086] The scanning electron microscope image of the barrier film prepared in Example 11 is as follows: Figure 4 As shown, through Figure 4 It can be seen that the flaky talc@TiO2 is filled in the TPU film substrate.
[0087] Performance Testing
[0088] The UV-Vis-NIR spectrophotometer was used to test and calculate the solar reflectivity. The infrared emissivity was tested using Fourier transform infrared spectroscopy. The helium transmittance of the membrane material was tested using the differential pressure method.
[0089] The membrane material made of commercial PTMG soft segment TPU is used as comparative example 1, the membrane material made of the membrane substrate solution of Example 1 (without adding filler) is used as comparative example 2, and the membrane material made of commercial TPU with 50 wt % TiO2 added is used as comparative example 3.
[0090] The performance test results are shown in the following table:
[0091]
[0092] Among them, the infrared emissivity test spectra of Example 1, Example 5, Example 10, Comparative Example 1, and Comparative Example 2 are as follows: Figure 5 As shown, the calculation formula for infrared emissivity is as follows:
[0093]
[0094] In the above formula, - infrared emissivity, -wavelength, -Relative spectral distribution of thermal radiation (293K), - infrared reflectivity, -Infrared transmittance.
[0095] It can be seen from Table 1 that the technical solution provided by the present invention can obtain a film material that takes into account the dual functions of gas barrier and photothermal control. It can be found from Comparative Examples 1 to 2 that the introduction of PEG in the soft segment can improve the gas barrier performance of the film material to a certain extent, while the introduction of PDMS can improve the infrared emissivity. It can be found from Comparative Example 3 and Examples 1, 4 and 8 to 15 that the contribution of flaky fillers (kaolin, mica, talc, expanded vermiculite, expanded perlite and diatomaceous earth) to gas barrier performance is greater than that of rod-shaped fillers (halloysite nanotubes, sepiolite, palygorskite) and greater than that of spherical fillers (TiO2). It can be found from Examples 1 to 5 that the solar reflectivity and gas barrier performance of the material are proportional to the content of the filler and the thickness of the film, and the infrared emissivity is not greatly affected by the filler. According to Examples 4, 6 and 7, it can be found that at the same thickness, the more PDMS content of the polyurethane, the lower the reflectivity and gas barrier performance of the material.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A barrier film, characterized in that: include: A film substrate and a filler filled in the film substrate; wherein the film substrate is a polyurethane containing a soft segment, the soft segment is a polydimethylsiloxane segment and a polyethylene glycol segment, and the molar ratio of the polydimethylsiloxane segment to the polyethylene glycol segment is 1:(1-10); the filler is a core-shell structure, the outer shell is titanium dioxide, the inner core is a natural mineral, and the shape of the inner core is sheet and / or rod; the filling amount of the filler in the barrier film is 30-65wt%.
2. The barrier film according to claim 1, characterized in that The natural mineral is one or more of sepiolite, kaolin, mica, talc, expanded vermiculite, expanded perlite, diatomaceous earth, palygorskite and halloysite nanotubes.
3. The barrier film according to claim 1, characterized in that The lamella thickness of the lamellar core is 20~100nm, and the dimension perpendicular to the thickness direction is 1~20μm; the length of the rod-shaped core is 1~10μm, and the diameter is 20~500nm.
4. The barrier film according to claim 1, characterized in that The titanium dioxide content of the filler is 20-40wt%.
5. A method for preparing the barrier film according to any one of claims 1 to 4, characterized in that: The following steps are involved: The filler is mixed with the film base material solution, coated, and dried to obtain a barrier film.
6. The preparation method according to claim 5, characterized in that: The filler is prepared according to the following steps: The acidic dispersion of the core material is mixed with tetrabutyl titanate to react to obtain a solid product; The solid product is calcined and crushed to obtain a core-shell structure filler with titanium dioxide as the outer shell.
7. The preparation method according to claim 5, characterized in that: The membrane substrate solution is prepared according to the following steps: Prepolymerizing diisocyanate, dihydroxy-terminated polydimethylsiloxane and polyethylene glycol in a solvent to obtain a prepolymer; The prepolymer is mixed with the chain extender for reaction, and after the reaction is completed, the solid content of the reaction product is adjusted with a solvent to obtain a polyurethane film substrate solution containing a soft segment.
8. The preparation method according to claim 5, characterized in that: The coating method is multiple scraping.
9. An inflatable bladder, characterized in that: The material of the inflatable bladder includes the barrier film described in any one of claims 1 to 4 or the barrier film prepared by the preparation method described in any one of claims 5 to 8.
Citation Information
Patent Citations
High-barrier weather-resistant thermal control polyurethane film and preparation method thereof
CN116063650A
Photo-thermal control film and preparation method and application thereof
CN118515965A